More insight into the mode of action of lipophilic antitumor drugs containing a platinum (II) fragment - Vanchanagiri, Kranthi (Journal of Medical Biomedical and Applied Sciences, 2017)
Cis-Diammine(1,1-cyclobutanedicarboxylato)platinum(II)) (Carboplatin 2) is a second generation platinum anticancer drug following Cis-diamminedichloroplatinum(II) (Cisplatin 1). In the present study Cisplatin and Carboplatin analogs are attached to the acid group of the bile acid via an ester link called as ChAPt(n)Cis and ChAPt(n)Carbo. The in vitro antitumor activity of Cisplatin 1 along with the corresponding ChAPt derivatives evaluated against a panel of five tumor cell lines of different histogenic origin. A series of biological methods starting from Sulforhodamine B (SRB) assay to determine IC50, Cell cycle analysis, Annexin-V assay and Caspase assays were performed with the aim to scrutinize the anticancer mode of action on HepG2 (hepatocellular car cinoma) cell line. The compounds exerted a dose dependent antiproliferative action at micro molar concentrations and the effect of these structural variations on anticancer activity was elaborated and discussed more in detail. To summarize, several compounds revealed significant antitumor activity and surprisingly the ChAPt(11)Cis and ChAPt(11)Carbo induce programmed cell death with molecular features different from each other, suggesting that both drugs induce apoptosis through different initial pathways.